2019
DOI: 10.1029/2018tc005373
|View full text |Cite
|
Sign up to set email alerts
|

Deformation, Annealing, Melt‐Rock Interaction, and Seismic Properties of an Old Domain of the Equatorial Atlantic Lithospheric Mantle

Abstract: We analyzed a set of mantle xenoliths from the Fernando de Noronha archipelago to constrain the roles of deformation, cooling, annealing, and melt percolation in the evolution of the mantle lithosphere of the equatorial Atlantic. The peridotites are dominantly lherzolites with coarse granular or porphyroclastic microstructures. Equilibrium temperatures range between 850 and 1,000 °C. Olivine crystal preferred orientations (CPO) have mainly orthorhombic patterns characterized by clear [100] and [010] point maxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 61 publications
4
26
0
1
Order By: Relevance
“…These processes are best recorded in those samples where recrystallization is concentrated in vein‐like domains (Figures 3g, 3h, 6a, and 6b), but peridotites with distributed recrystallization also often show a clear spatial association between pyroxene enrichment and recrystallization (Figure S1). Similar partial recrystallization of initially coarse‐porphyroclastic microstructures has been described in peridotite xenoliths from Fernando de Noronha Island in the Equatorial Atlantic (Liu et al, 2019). In the latter, decrease in Mg# and Ni content and increase in Ca content in olivine limited to a vein‐like recrystallized domain has been documented, corroborating the role of reactive melt transport in the development of the recrystallized domains.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…These processes are best recorded in those samples where recrystallization is concentrated in vein‐like domains (Figures 3g, 3h, 6a, and 6b), but peridotites with distributed recrystallization also often show a clear spatial association between pyroxene enrichment and recrystallization (Figure S1). Similar partial recrystallization of initially coarse‐porphyroclastic microstructures has been described in peridotite xenoliths from Fernando de Noronha Island in the Equatorial Atlantic (Liu et al, 2019). In the latter, decrease in Mg# and Ni content and increase in Ca content in olivine limited to a vein‐like recrystallized domain has been documented, corroborating the role of reactive melt transport in the development of the recrystallized domains.…”
Section: Discussionsupporting
confidence: 68%
“…In (a), labels indicate the samples with CPO presented in Figure 12. J and BA indexes for mantle xenoliths from Fernando de Noronha (Liu et al, 2019) and Canary Islands (Vonlanthen et al, 2006) in the Atlantic Ocean and French Polynesia in the Pacific Ocean (Tommasi et al, 2004) recalculated using with the same CPO analysis parameters as in the present study are shown for comparison in (a).…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…Using the former method, we obtained d values that are about 1.6 times larger than values given by the latter method from the same microstructures (see Figure A4 in Yabe et al, 2020). Although their size ratio is a function of the grain‐size distribution, we can reasonably consider a grain size of 1 mm in Equation 20a based on the oceanic lherzolite described by Liu et al (2019). Obviously, it is premature to conclude the predominance of a millimeter‐scale grain size in the mantle with such limited observations, leaving the issue for future studies.…”
Section: Discussionmentioning
confidence: 99%